Magnetic Resonance Imaging at 1.5 T after Pediatric Cochlear Implantation without Magnet Removal. (2nd September 2014) - Gupta, Sachin; Isaacson, Brandon; Roland, Peter S.; Kutz, Joe W.; Booth, Tim N.; Jacob, Roy; Morriss, Michael C
Abstract : Objectives: (1) Assess the safety of 1.5 T magnetic resonance imaging (MRI) in pediatric patients with cochlear implants (CIs) and internal magnets. (2) Assess artifacts created by CI magnets. Methods: A retrospective chart review was performed of pediatric CI patients who underwent 1.5T MRI at a university children's hospital. Binding of the CI magnet was performed before MRI, using mold material and a compressive gauze dressing. Patients were assessed for ability to complete the MRI, imaging artifact from the CI magnet, magnet position, and CI function following MRI. Results: Four patients (mean age 65 months; range, 19‐108 months), and a total of 6 CIs (2 bilateral), underwent 1.5 T MRI scans. There were 3 brain MRI studies and 1 spine. Informed parental consent was obtained. Clinical indications included leukodystrophy (2), hypertonia (1) and dystonia (1). Devices from 2 manufacturers were scanned. A CT scan was performed before the MRI scan in three‐fourths of patients to assess bone thickness adjacent to the magnet. Three patients had MRI under anesthesia. The CI produced an artifact with a mean maximal AP dimension of 10.8 mm (range 7.5‐15 mm) and a transverse of 5.7 mm (range 5.5‐6 mm). Greatest image distortion occurred with bilateral implants. There was no change in magnet position or CI function after the MRI in all cases. Conclusions: Pediatric patients may safely undergo 1.5 T MRI after CI without removal of the magnet if the device is tightly bound beforehand and strict safety protocols are followed. There are limitations to brain imaging due to artifacts.